Updates on Advanced Therapies for Acute Pulmonary Embolism - Bikdeli, Bavand; Bikdeli, Behnood (International Journal of Cardiovascular Practice, 2016)
Venous thromboembolism is the third common vascular disease after acute myocardial infarction and stroke, and acute pulmonary embolism (PE) remains as the most common preventable cause of in-hospital mortality. In addition to routine anticoagulant therapy, several advanced treatment options have been introduced over the past three decades. We provide a succinct and contemporary summary of the evidence base and important indications for inferior vena caval filter placement, systemic and catheter-based thrombolytic therapy, as well as percutaneous and surgical thrombectomy. Appropriate case selection for advance therapies for PE could minimize the adverse effects and costs, while optimizing the outcomes.